Effectiveness of Construction and Presentation of Physical models by First MBBS students as an active Learning tool in Physiology - Anju Asia; Tripti Srivastava; Sapana Motewar (Mashhad University of Medical Sciences, 2023)
Background: Understanding Physiological concepts is the backbone of Medicine. Active learning strategies can strengthen this process. The aim of this study was to introduce Model construction and its presentation as a self-directed learning tool (SDL) for the subject of Physiology.Method: The 2nd semester, 1st MBBS students Batch 2021-2022 actively worked in groups to construct physical models. Outcome of the educational intervention was calculated through post test scores, assessment of the models by judges, and student feedback regarding the SDL activity of model construction and presentation.Results: The comparison between scores for pre-test (8.1 ± 0.8) and post-test (12.8 ± 2.6) taken at the end showed that there was a statistically significant difference (p<0.05) in the scores. Evaluation of the model showed that groups scored well for all criteria except in their ability to answer queries. Students strongly supported Competitiveness (87%) and group discussions (79%). Some agreed that this activity was time consuming and tiring (45%).Conclusion: Application of a Physiological concept in form of case scenarios acted as a trigger hence the search for answers initially generated interest and curiosity. The active engagement learning strategy resulted in knowledge gain as evidenced by student's performance in the post test and their ability to represent information on a physical model. Conventional teaching can be accompanied by similar strategies which are realistic, assure student participation and desirable learning outcomes.